Marketing Optimalisasi Digital Marketing Usaha Mikro Ecoprint DimDimArt Dengan Laman Web Sebagai Media Integrasi Multiplatform - Nugraha, Dyka Ardhana; Ichyaussunnah, Muhammad; Zulhirom, Moh. Afikul Dwi; Ananda, Mohammad Yusuf Putra; Aisahwaya, Vicky; Aulia, Ade Zahra; Fithrotin, Annisa Elva; Fransisca, Khofifah Indra; Afandi, Akhmad Jazuli (Aktualisasi Pengabdian Masyarakat, 2025)
The community service activity for the micro business Ecoprint DimDimArt aims to optimise digital marketing through the development of a website as a multiplatform integration medium. The Participatory Action Research (PAR) method was used to actively involve business owners in all stages, from problem identification, technical assistance, content strategy design, to sustainability evaluation. The intervention focused on creating a website that integrates Instagram, WhatsApp Business, TikTok, and other digital platforms into a centralised link. The results showed an increase in website traffic, customer engagement, and the effectiveness of product information distribution. Technical challenges related to content updates were addressed through training, written guidelines, and ongoing support. These findings support the concept of Integrated Marketing Communication (IMC) and demonstrate that a simple yet functional website can be an effective solution for SMEs to enhance competitiveness without significant investment. This model has the potential to be replicated for other micro-enterprises with adjustments tailored to their specific needs.